Determinants of small and medium enterprises performance in the Malaysian auto-parts industry - Mohd Rosli Mohamad (Academic Journals, 2011)
This paper examines factors determining the performance of SMEs in the Malaysian auto-parts industry. Using a multiple regression analysis, it is evident that firm age and foreign equity are significantly related to the performance of the firms. This consolidates earlier expectations and studies that age and foreign equity ownership do matter to SMEs performance. These findings provide an important signal for SMEs for entering joint ventures with foreigners in order to achieve better performance and more importantly to compete in the growing open market mechanisms. Only through joint ventures, foreigners would be eager to transfer a package of required assets, including technological, marketing and managerial skills to the local partners. Further research should be conducted to determine the role played by foreigners, who are responsible for improving SMEs performance in the auto-parts industry. Future studies should also incorporate intangible performance measures, such as customer satisfaction, competitive position and quality of product.